Exploring Finnish EFL Teachers’ Perceived Technological Pedagogical Content Knowledge (TPACK) following Emergency Remote Teaching: A Quantitative Approach - Lamminpää, Maija (My University, 2021)
In Finland, the current National Core Curriculum (NCC) greatly emphasizes developing students’ skills in information and communication technologies (ICT). Mastering such skills is therefore expected from teachers, as well. However, research has indicated that there is variation in the extent to which technology is integrated into teaching, partially because of differences in teacher skills. Technological Pedagogical Content Knowledge (TPACK) is a framework for understanding and describing what teachers need to know in order to effectively teach with technology. The purpose of this thesis is to explore the current level of perceived TPACK among Finnish teachers of English as a foreign language (EFL). The level of TPACK is studied in general and with respect to teachers of different age groups and with varying amounts of teaching experience. In addition, the thesis investigates the impact that Finnish EFL teachers’ feel the period of emergency remote teaching (ERT), caused by the COVID-19 pandemic in spring 2020, had on their ICT skills. A total of 69 Finnish EFL teachers participated in the study, which utilized the TPACK instrument developed for EFL teachers by Baser, Kopcha & Ozden (2016). The data were gathered through an online survey and analyzed with the statistical analysis software SPSS. The results indicate that Finnish EFL teachers’ perceived level of knowledge is consistently high in all TPACK domains. Due to the small variance across participants, only minor differences could be detected in the scores for some TPACK domains when examined with relation to age and teaching experience. Furthermore, the majority of the participants reported ERT had improved their ICT skills, while a fifth of the participants already had such high skills that they were not affected by ERT. Although the findings indicate a high level of TPACK among Finnish EFL teachers, the results cannot be generalized to the entire population. In order to obtain more precise and generalizable results, it is suggested that a TPACK instrument more suitable for the Finnish context is developed, and that the sample of participants is selected through sampling methods that ensure more representativeness of the entire population. Thus, the results provide valuable information for future TPACK research in Finland.
Keywords: language teaching, technology, English as a foreign language, emergency remote teaching, TPACK, ICT